Mendenhall Glacier / Suicide Basin outburst flood data, 2018-2019 - Christian Kienholz; Jamie Pierce; Gabriel Wolken; Jason Amundson; Eran Hood (Arctic Data Center, 2020)
Mendenhall Glacier, Alaska, has been experiencing annual outburst floods that originate from Suicide Basin, an ice marginal basin. As part of a project aimed at understanding the dynamics of these floods and the threat that they pose, we collected (1) aerial imagery from an unmanned aerial vehicle that was used to construct orthomosaics, digital elevation models, and velocity fields of the ice-choked basin, (2) LIDAR data that was used to construct additional digital elevation models, (3) photos from the Alaska High-Altitude Aerial Photography project (AHAP) that was used to construct an orthomosaic, (4) glacier mass balance measurements, (5) meteorological data, and (6) water level measurements of the water in Suicide Basin.